Pendidikan Spiritual Siswa Melalui Puasa Senin-Kamis Di Sekolah Menengah Pertama Muhammadiyah 1 Kartasura - Rosidi, Muhammad Faruq Abbad; Salim, Hakimuddin (Jayapangus Press, 2025)
Spiritual education has an important role in shaping the character of students, especially at the junior high school level. One of the efforts to strengthen spiritual education in schools is through the implementation of the Monday-Thursday Fasting program. This study aims to determine the implementation of the Monday-Thursday Fasting program and its impact on the development of students' spiritual character at SMP Muhammadiyah 1 Kartasura. This research uses a descriptive qualitative approach with data collection techniques through direct observation, interviews with teachers and students, and analysis of relevant documents. The results showed that this program has been running effectively and structured. The Monday-Thursday Fasting program succeeded in increasing discipline, patience, emotional control, sincerity, and forming social solidarity among students. Observations showed a decrease in negative verbal behavior and increased spiritual awareness. Despite obstacles such as limited control outside the school environment and decreased student stamina, the school was able to make adjustments through special policies such as compressed class schedules and student health support. Program evaluation is carried out on an ongoing basis through teacher observation and regular communication with parents. These findings support Bronfenbrenner's theory on the importance of school and family interactions in shaping student character as well as ta'dib theory in Islamic education. In conclusion, the Monday-Thursday Fasting program contributes greatly to building a religious school environment, improving students' spiritual intelligence, and becoming a strategic model in the development of character education based on Islamic values in schools.